LACK OF EFFECT OF PRETREATMENT ON THE VIABILITY OF MACADAMIA (Macadamia integrifolia) SEED - Hasanah, Maharani; ., Sukarman; ., Sukarman; Rusmin, Devi; Rusmin, Devi (Indonesian Journal of Agricultural Science, 2002)
One problem in developing macadamia in Indonesia is the limited availability of good quality seed. Viability of the seed is easily lost and erratic, and the seed has long dormancy periods. The objective of the study was to find a method for enhancing germination percentage of macadamia seed. The study evaluated different pretreatments of macadamia seeds before planting. The pretreatments were period of fermentation, i.e., 0, 1, 2, 3, 4, 5, 6, and 7 daysone day each soakingdrying-soakingone day each drying-soaking-dryingand alternate drying-soaking until the seeds were cracked. The treatments were arranged in completely randomized design. Results showed that no treatment significantly affected percentage of seed germination, index of speed of germination, number of leaves, and dehydrogenase enzyme activity, but treatments significantly affected seedling height and electric conductivity of seed leakage solution. Seed germination percentage ranged from 66.67 to 86.67.